2009
DOI: 10.1093/ejechocard/jep058
|View full text |Cite
|
Sign up to set email alerts
|

Atrial reservoir function by strain rate imaging in asymptomatic mitral stenosis: prognostic value at 3 year follow-up

Abstract: Atrial myocardial deformation properties, assessed by SRI, are abnormal in asymptomatic patients with rheumatic MS. The degree of this impairment is predictor of events in a 3 year follow-up. SRI could be helpful in decision-making of asymtomatic patients with MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0
9

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(86 citation statements)
references
References 31 publications
2
75
0
9
Order By: Relevance
“…Myocardial deformation imaging based on tissue Doppler or 2D speckle-tracking has been introduced as a more sophisticated approach for the evaluation of global and regional function of LA walls including their properties during the reservoir phase [31,32]. Caso et al demonstrated that the assessment of atrial reservoir function by myocardial deformation imaging may be helpful in decisionmaking of asymptomatic patients with mitral stenosis [33]. Functional parameters derived from myocardial deformation imaging, especially strain rate, may be less dependent on loading conditions of the cardiac chamber as has been shown for LV [34].…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial deformation imaging based on tissue Doppler or 2D speckle-tracking has been introduced as a more sophisticated approach for the evaluation of global and regional function of LA walls including their properties during the reservoir phase [31,32]. Caso et al demonstrated that the assessment of atrial reservoir function by myocardial deformation imaging may be helpful in decisionmaking of asymptomatic patients with mitral stenosis [33]. Functional parameters derived from myocardial deformation imaging, especially strain rate, may be less dependent on loading conditions of the cardiac chamber as has been shown for LV [34].…”
Section: Discussionmentioning
confidence: 99%
“…The difference between maximum and minimum LA volume divided by the minimum LA volume is used as index of atrial compliance [4, 5]. …”
Section: Standard Echocardiographic Methodsmentioning
confidence: 99%
“…Evaluations have included patients with hypertension (19), hypertrophic cardiomyopathy (79,110,111), Fabry disease (112), atrial septal defects (113), valvular stenosis (114,115) and AF (109,116).…”
Section: La Strain and Strokementioning
confidence: 99%